2008
DOI: 10.1002/qua.21893
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical and experimental study on manipulating the structure and properties of carbon nanotubes using substitutional dopants

Abstract: ABSTRACT:We examine the possibility of controlling nanotube growth and simultaneously manipulating the nanotube properties by adding elements in minute amounts (such as nitrogen, phosphorous, and sulfur) that are different from carbon and the metal catalyst during the growth process. This procedure is shown to be capable of producing bamboo-type morphologies, heterodoped carbon nanotubes, and Y-junctions. This also represents a critical step toward tailoring properties and controlling nanotube architectures, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 70 publications
(99 reference statements)
3
62
1
Order By: Relevance
“…The iron content in Fe@N-C-600 was measured to be 0.4 wt% by XPS. Fe@N-C-800 and Fe@N-C-900 display the characteristic bamboo-like morphology of CNTs (Figure 2c-f), which was attributed to the presence of pentagon structures in the graphite network due to nitrogen doping [45]. Iron nanoparticles are observed to be encapsulated in the CNTs.…”
Section: Resultsmentioning
confidence: 93%
“…The iron content in Fe@N-C-600 was measured to be 0.4 wt% by XPS. Fe@N-C-800 and Fe@N-C-900 display the characteristic bamboo-like morphology of CNTs (Figure 2c-f), which was attributed to the presence of pentagon structures in the graphite network due to nitrogen doping [45]. Iron nanoparticles are observed to be encapsulated in the CNTs.…”
Section: Resultsmentioning
confidence: 93%
“…These authors also found that pyridine-type defects promote localized states near the valence-band, and acts as an acceptor. Other studies, performed by Sumpter et al 18 have demonstrated the possibility of controlling the nanotube growth by adding nitrogen, phosphorus, and sulfur atoms in small concentrations. Subsequent studies on the adsorption of metal atoms or molecules on graphite, 19 graphene, 20 and nanotubes 21 together with defects and nitrogen as a dopant, have been reported, as well as the influence of the nitrogen atoms on the radial breathing mode in carbon nanotubes.…”
Section: Introductionmentioning
confidence: 97%
“…10 Sumpter and co-workers 11,12 have studied the growth of N-CNTs by means of experiment and density-functional theory (DFT) calculations. They found that nitrogen atoms are prone to localize at two-coordinated sites or as dangling C−N bonds.…”
Section: Introductionmentioning
confidence: 99%